LIVROS DIDÁTICOS E POLUIÇÃO AMBIENTAL: MAIS DO QUE UMA ESCOLHA, UMA DECISÃO - Cunha, Mariana Freitas de Souza; Nascimento, Nadine Anne Cruz do; Miguel, João Rodrigues (Revista de Educação, Ciências e Matemática, 2014)